Agama dan Modernitas dalam Praktik Ritual Mandi Safar di Kayong Utara - Wahab, Wahab; Hariansyah, Hariansyah; Hayati, Dewi Nur (Jurnal Studi Agama dan Masyarakat, 2019)
The Sungai Jambu Malay society believes that the Safar Month brings curses and illness. Avoiding this, the local community does the Safar bath ritual by reading selected shurah in the Qur